Orchid bee fauna (Hymenoptera: Apidae: Euglossina) of Atlantic Forest fragments inside an urban area in southeastern Brazil - Nemésio,André (2007)
Male orchid bees were collected by chemical baiting in four forest fragments in parks of the city of Belo Horizonte, Minas Gerais, southeastern Brazil. One thousand three hundred and twenty-five males belonging to 14 species were captured within one year. The capture data were compared through correlation tests. The data suggest that abundance of orchid bees tend to increase with fragment size, although no correlation between species richness and fragment size was obtained. The results presented herein suggest that forest fragments in a large city may be of importance concerning conservation of orchid-bee faunas.